Joseph Goebbels : life and death - Thacker, Toby 1957- (Palgrave Macmillan, 2009)
"This book is an insightful new biography of Joseph Goebbels, Propaganda Minister of the Third Reich and one of the most important and troubling figures of the twentieth century. The first account to use all of Goebbels' surviving diaries, it sheds new light on his personality, private life and political convictions, as well as his relationship with Hitler"--Provided by publisher